READING ANXIETY IN ENGLISH AS A FOREIGN LANGUAGE FOR UNDERGRADUATE STUDENTS IN INDONESIA - Azizatuz Zahro Al Faruq (Siliwangi University, 2019)
Exploring students’ anxiety and its sources in a foreign language have highly paid the attention of many researchers in the field of foreign language teaching and learning, especially in English Language Teaching (ELT). On the other hand, the anxiety and its sources of foreign language learning itself affect the achievement of specific language skills such as reading which has infrequently been investigated. Some studies focused only on Foreign Language Classroom Anxiety and/or also Foreign Language Speaking Anxiety in EFL undergraduate students. Thus, this research was intended to investigate students’ reading anxiety in English as a Foreign Language (EFL) of the undergraduate student class. There were 37 non-English program undergraduate students participated in this research. The research method was a case study. The data were collected using questionnaires that measured students’ anxiety and the sources of students’ anxiety in reading context, Foreign Language Reading Anxiety Scale designed by Saito et al. (1999) and the questionnaire developed by Ahmad et al. (2013). The research found out that most students identified anxiety in medium level. The sources of students' reading anxiety were based on the material features including unknown vocabulary and unfamiliar culture as the most sources. The personal factors found were afraid of making errors which is less than worry about reading effect. The implication is the lecturers can assist foreign language students to reduce foreign language reading anxiety by improving the students’ self-confidence to deal with the personal factor.